Mechanisms and therapeutic potential of microRNAs in hypertension - Shi, Lijun (Drug Discov Today, 2015)
Hypertension is the major risk factor for the development of stroke, coronary artery disease, heart failure and renal disease. The underlying cellular and molecular mechanisms of hypertension are complex and remain largely elusive. MicroRNAs (miRNAs) are short, noncoding RNA fragments of 22–26 nucleotides and regulate protein expression post-transcriptionally by targeting the 3′-untranslated region of mRNA. A growing body of recent research indicates that miRNAs are important in the pathogenesis of arterial hypertension. Herein, we summarize the current knowledge regarding the mechanisms of miRNAs in cardiovascular remodeling, focusing specifically on hypertension. We also review recent progress of the miRNA-based therapeutics including pharmacological and nonpharmacological therapies (such as exercise training) and their potential applications in the management of hypertension.